Conflicto armado y terrorismo en Colombia. El terrorismo de las Farc-EP de acuerdo con la Jurisprudencia de la Corte Constitucional colombiana (2016)
In Colombia he denied the existence of the internal armed conflict and on other occasions it was recognized that internal disturbances and tensions and the Farc-EP did not meet the requirements of the Geneva Conventions and its additional protocols; accordingly aspects of armed conflicts were not decisive to point out that all had an internal armed conflict and, instead, often in the twentieth century and so far this is said there was a terrorist threat. On the issue the Constitutional Court has been raising issues that have to do with the internal armed conflict in Colombia and with it has dealt with terrorism as one of the main problems generate violence. The issue of terrorism carried out by the Farc-EP specifically addresses the attention as this group is now (2015) considered as one of the parties to the armed conflict that occurred in Colombia for five decades. This article aims to analyze key projection terrorism in an eventual post-determining aspects of the jurisprudence of the Colombian Constitutional Court in relation to the internal armed conflict and the impact these decisions have on terrorism happened in this country.